Transforming growth factor-beta 3 intron 5 polymorphism as a screening marker for non-syndromic cleft lip with or without cleft palate - GÜNEY, AHMET İLTER; ULUCAN, KORKUT (SPANDIDOS PUBL LTD, 2012)
In this study, we evaluated the effect of transforming growth factor beta 3 intron 5 position +104 A -> G (TGF-beta 3 IVS5+104AG) transition in patients with a non-syndromic cleft lip with or without cleft palate (NSCL/P). A total of 68 patients and 114 controls were recruited for the study. A genotyping procedure was carried out using the PCR-RFLP method. For statistical analysis, the Chi-square test was used to compare data between the patient and control groups. The frequencies of the AA, AG and GG genotypes were 24, 29 and 47%, respectively, for the patients and 54, 36 and 10%, respectively, for the control group. The GG genotype and G allele were significantly different in the patient group compared with the control (p=0.0001). We conclude that SfaN1 polymorphism in TGF-beta 3 may be a good screening marker for the prediction of NSCL/P in patients. However, more studies with extended sample numbers should be carried out to clarify the effect of the examined gene region on NSCL/P.
Keywords: transforming growth factor beta; non-syndromic cleft lip with or without palate; polymorphism; screening; patients; NONSYNDROMIC ORAL CLEFTS; CANDIDATE GENES; OROFACIAL CLEFTS; AND/OR PALATE; TGFB3; POPULATION; ASSOCIATION; JAPANESE; MSX1